INFLUENCE OF SEDIMENTATION FACIES AND DIAGENESIS TO SANDSTONE RESERVOIR OF WALAT FORMATION IN CIBADAK AREA, SUKABUMI DISTRICT, WEST JAWA - Bima, Rengga
Reservoir porosity is an important parameter for petroleum exploration and production. The porosity of sandstone reservoir is mainly controlled by rock texture and diagenesis processes. Theoretically, sediment facies and diagenesis with the same depth will be formed specifically for their depositional environment, usually having similar reservoir porosity characteristics. This research aims to study the effect of depositional facies and diagenesis on the development of the Walat Formation’s sandstone porosity. In this research, stratigraphic cross section measurements were carried out on four trajectories and observations of sandstone outcrops which were then carried out by lithofacies analysis, facies association, depositional environment, petrographic analysis, diagenesis analysis and porosity analysis. The Walat Formation is composed of sandstones, conglomerates, interbedded of sandstone and claystone that has siltstone-intercalated with claystone that has carbon-intercalated. From the four trajectories, the depositional facies were identified which consisted of floodplain, levee, crevasse splay, stacking channel, point bar and geometry bar channel. These depositional facies characterize the river depositional environment which has a system between braided river and low sinuosity river that develops to meandering river up to delta. Twenty-six sandstone samples have been used to petrographic observations and diagenesis analysis and three samples have been used to routine core measurement. The result is litharenite, quartz arenite and sublitharenite sandstones. The diagenesis process that occurs is compaction, recrystallization, cementation, dissolution, and replacement. The presence of rock texture, mineralogy, matrix, cement and diagenesis can increasing or decreasing the porosity value. Based on these observations, the factors that influence the porosity value of a rock related to reservoir quality are depositional facies, rock texture, mineralogy composition, matrix, cement and diagenesis processes. The results of this research are expected to be a model of sandstone reservoir quality assessment and as a contribution to science in oil and gas exploration in Indonesia.